Process for disassembling and recycling lithium iron phosphate batteries
Patent Information
- Application Number
- CN202310059532.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-01-20
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2043-01-20
AI Technical Summary
Existing lithium iron phosphate battery recycling technologies involve complex reaction processes, incomplete separation, and discontinuous regeneration processes, resulting in low lithium and iron recovery rates and reduced performance of regenerated lithium iron phosphate.
Regenerated lithium iron phosphate material is prepared by disassembling lithium iron phosphate batteries, grinding and mixing with phosphoric acid solution, ultrasonic treatment, electrolytic separation of lithium and iron, adjusting pH value to precipitate, adding alkaline earth metal salt and sodium carbonate to precipitate, and calcining.
The reaction path was simplified, the recovery rate of lithium and iron was improved, energy consumption was reduced, the battery-grade purity and performance of regenerated lithium iron phosphate were maintained, and the generation of solid waste was avoided.
Smart Images

Figure CN116315213B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of lithium-ion battery recycling technology, specifically relating to the dismantling and recycling process of lithium iron phosphate batteries. Background Technology
[0002] With the increasing production and market launch of lithium-ion batteries, a significant technical challenge has emerged: the need to recycle large quantities of used lithium-ion batteries. Currently, power lithium batteries primarily utilize ternary cathode materials and lithium iron phosphate (LFP) cathode materials. Due to the low Co content and high cost of ternary cathode materials, research on their recycling and regeneration is more extensive. However, LFP, with its olivine structure, boasts abundant resources, environmental friendliness, long lifespan, and good thermal stability, attracting widespread attention and becoming a hot research topic in lithium-ion battery cathode materials. In 2021, the market share of LFP cathode materials increased from 24% to 43%, while the market share of ternary cathode materials slightly declined from 46% to 38%. Therefore, the dismantling and recycling of LFP batteries has become a key focus.
[0003] In the past, the recycling of lithium iron phosphate batteries mainly focused on the recovery of elements. CN109264748B adds alkali to the positive electrode powder to dissolve aluminum, the resulting filter mud is leached with acid and reducing agent, impurities are precipitated by adding alkali, and then solid sodium carbonate is added to obtain lithium carbonate, while recovering lithium and iron elements at the same time.
[0004] CN109811125B utilizes reduction methods to reduce iron and phosphorus to low valence states, while lithium iron phosphate is decomposed into lithium compounds and iron-phosphorus alloys. Magnetic separation is then performed for recycling, achieving complete recovery of phosphorus, iron, and lithium elements from waste lithium iron phosphate.
[0005] However, apart from lithium, the other elements in lithium iron phosphate are relatively inexpensive. Completely converting lithium iron phosphate into lithium, iron, phosphorus, and other elements is energy-intensive and costly. Furthermore, if these elements need to be reused, they must be further converted into usable cathode materials, which lengthens the conversion chain and reduces the recycling rate.
[0006] Therefore, based on existing lithium iron phosphate recycling technology, a new dismantling and recycling process needs to be considered so that the recovered lithium and iron elements can be reused as soon as possible to form regenerated lithium iron phosphate. This would avoid element loss during the recycling process and maintain the battery's regeneration quality as much as possible during the regeneration process, thus preventing a decrease in battery performance. Summary of the Invention
[0007] Based on this, the present invention provides a dismantling and recycling process for lithium iron phosphate batteries, which solves the technical problems in the prior art such as complex reaction procedures, incomplete separation, and discontinuous regeneration process when extracting elements from lithium iron phosphate cathode materials, and can ultimately provide battery-grade pure regenerated lithium iron phosphate cathode materials.
[0008] To achieve the above objectives, the present invention provides the following technical solution:
[0009] According to one aspect of the present invention, a dismantling and recycling process for lithium iron phosphate batteries is provided, comprising the following steps:
[0010] S1: Disassemble and grade the lithium iron phosphate battery to obtain degraded lithium iron phosphate cathode material for later use;
[0011] S2: Grind the degraded lithium iron phosphate cathode material, then mix it with phosphoric acid solution, and sonicate it. Let it stand, separate the upper clear liquid, and retain the lower uniform slurry treated with phosphoric acid.
[0012] S3: Load the slurry onto the positive electrode substrate, compact it to remove the remaining phosphoric acid residue, dry it to prepare the anode, and recover the phosphoric acid solution from steps S2 and S3 for later use.
[0013] S4: Select an acid-resistant stainless steel plate as the cathode, use the phosphoric acid solution from steps S2 and S3 as the electrolyte, apply voltage to perform electrolysis until lithium and iron in the positive electrode slurry dissolve.
[0014] S5: Adjust the pH of the dissolution solution to 1.5-2, then heat under reflux for 3-8 hours to precipitate ferric phosphate, and then filter and separate it for later use;
[0015] S6: Add alkaline earth metal nitrate to the filtrate from S5 and heat to 50-80℃ to precipitate alkaline earth metal phosphate. Then, filter and separate the precipitate at this temperature.
[0016] S7: Add sodium carbonate aqueous solution to the lithium-containing filtrate obtained in S6, and control the concentration of sodium carbonate to keep the pH value between 9 and 11 to obtain lithium carbonate precipitate, and wash and dry it.
[0017] S8: Add the iron phosphate obtained in S5 and the lithium carbonate obtained in S7 to an organic acid solution, grind and stir for 30-60 minutes, then dry the mixture, granulate it and calcine it at 600-700℃ for 4-8 hours to obtain the regenerated lithium iron phosphate material.
[0018] In some embodiments of the present invention, the phosphoric acid solution in step S2 is partially derived from the phosphoric acid solution recovered in steps S2 and S3, and the concentration of the phosphoric acid solution is prepared to be 0.2-1.5 mol / L, more preferably 0.5-1 mol / L.
[0019] In some embodiments of the present invention, the degraded lithium iron phosphate cathode material in step S2 is ground to 50-500 mesh, ultrasonically treated for 20-60 min, and left to stand for 2-24 h. More preferably, the degraded lithium iron phosphate cathode material is ground to 100-300 mesh, ultrasonically treated for 30-40 min, and left to stand for 5-16 h.
[0020] In some embodiments of the present invention, the positive electrode substrate in step S3 is a porous conductive carbon material, wherein the average pore size is 10-200 μm, and more preferably 50-100 μm.
[0021] In some embodiments of the present invention, the voltage applied during electrolysis in step S4 is 1V-4V, more preferably 1.5V-3V, and the concentrations of lithium ions and iron ions in the solution are detected until the concentrations no longer change.
[0022] In some embodiments of the present invention, in step S5, the pH value of the dissolution solution is adjusted by adding phosphoric acid, and the reflux temperature is 75-90°C.
[0023] In some embodiments of the present invention, the alkaline earth metal nitrate in step S6 is calcium nitrate and / or magnesium nitrate.
[0024] In some embodiments of the present invention, the concentration of sodium carbonate in step S7 is in the range of 1 mol / L-3 mol / L, and more preferably 1.5-2.5 mol / L.
[0025] In some embodiments of the present invention, in step S8, iron phosphate and lithium carbonate are ground to an average particle size of 100-500 nm, more preferably 150-300 nm, and the organic acid is at least one of acetic acid and maleic anhydride.
[0026] In some embodiments of the present invention, a carbon source is further added and mixed in step S8, wherein the carbon source is selected from at least one of glucose and sucrose.
[0027] Compared with the prior art, the present invention has at least the following beneficial effects:
[0028] 1. The degraded lithium iron phosphate cathode material is ground and then thoroughly mixed with a phosphoric acid solution to ensure complete immersion of the cathode material in the phosphoric acid. Electrolysis is then used to fully react the lithium and iron in the degraded lithium iron phosphate cathode material, forming soluble iron phosphate and lithium phosphate, thus improving the recovery rate of lithium and iron. Simultaneously, the phosphoric acid is partially recycled in steps S2 and S3 to save costs.
[0029] 2. By utilizing the reduced solubility of ferric phosphate under acidic conditions and high-temperature reflux, ferric phosphate and lithium phosphate solutions are separated, while most of the ferric phosphate is retained as a regenerated raw material.
[0030] 3. The entire process avoids multiple calcination, drying and evaporation processes as much as possible, reducing energy consumption. Furthermore, based on the characteristics of battery-grade lithium iron phosphate, by retaining some of the doping elements added during the recycling process, the need for additional doping elements after purification is reduced.
[0031] 4. The entire regeneration reaction path is simple, and the precipitate or filtrate obtained in each step can be reused in the whole process or used as solidified phosphate fertilizer, thus avoiding the generation of solid waste. Attached Figure Description
[0032] Figure 1 The process flow diagram for dismantling and recycling lithium iron phosphate batteries provided by this invention. Detailed Implementation
[0033] Although the invention has been described to a certain extent, it is apparent that appropriate variations can be made to the various conditions without departing from the spirit and scope of the invention. It is understood that the invention is not limited to the described embodiments, but falls within the scope of the claims, which include equivalent substitutions for each of the elements.
[0034] The terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of technical features indicated. Therefore, a feature defined as "first" or "second" may explicitly or implicitly include one or more of that feature. In the description of this application, "multiple" means two or more, unless otherwise explicitly specified.
[0035] According to one aspect of the present invention, a process for extracting degraded ternary lithium battery cathode material is provided, comprising the following steps:
[0036] S1: Disassemble and classify the lithium iron phosphate battery to obtain degraded lithium iron phosphate cathode material for later use; the disassembly and classification process in step S1 is a common physical disassembly and classification process in the field of waste battery recycling, and the degraded lithium iron phosphate cathode material is finally obtained from the disassembly.
[0037] S2: The degraded lithium iron phosphate cathode material is ground, then mixed with a phosphoric acid solution, and subjected to ultrasonic treatment. After standing, the supernatant is separated, and the lower homogeneous slurry treated with phosphoric acid is retained. In step S2, the phosphoric acid solution is used to further wash and dissolve the degraded lithium iron phosphate cathode material, and to fully wet the ground cathode material, preparing it for complete dissolution during electrolysis in step S3. In some embodiments of the present invention, the phosphoric acid solution in step S2 is partly derived from the phosphoric acid solution recovered in steps S2 and S3, and the concentration of the phosphoric acid solution is prepared to be 0.2-1.5 mol / L, more preferably 0.5-1 mol / L. In some embodiments of the present invention, in step S2, the degraded lithium iron phosphate cathode material is ground to 50-500 mesh, ultrasonically treated for 20-60 min, and stood for 2-24 h, more preferably ground to 100-300 mesh, ultrasonically treated for 30-40 min, and stood for 5-16 h.
[0038] S3: The slurry is loaded onto the positive electrode substrate, compacted to remove the remaining phosphoric acid residue, and dried to prepare the anode. The phosphoric acid solution from steps S2 and S3 is recovered for later use. In some embodiments of the present invention, the positive electrode substrate in step S3 is a porous conductive carbon material, wherein the average pore size is 10-200 μm, more preferably 50-100 μm. By using a porous conductive carbon material, the slurry is more easily loaded onto the positive electrode substrate.
[0039] S4: An acid-resistant stainless steel plate is selected as the cathode, and the phosphoric acid solution from steps S2 and S3 is used as the electrolyte. Electrolysis is performed by applying voltage until lithium and iron in the positive electrode slurry dissolve. In steps S3 and S4, lithium and iron elements are directly dissolved from lithium iron phosphate into the electrolyte through electrolysis of the positive electrode slurry. Since the electrolyte used is a phosphoric acid solution, which has the same anionic fraction as lithium iron phosphate, lithium phosphate and iron phosphate salts are ultimately formed, which are easy to regenerate in subsequent processes. In some embodiments of the present invention, the voltage applied for electrolysis in step S4 is 1V-4V, more preferably 1.5V-3V, and the concentrations of lithium ions and iron ions in the solution are detected until the concentrations no longer change.
[0040] S5: Adjust the pH of the dissolution solution to 1.5–2, then heat under reflux for 3–8 hours to precipitate ferric phosphate, which is then filtered and separated for later use. In step S5, the solubility of ferric phosphate decreases under acidic conditions and high-temperature reflux, allowing for the separation of ferric phosphate and lithium phosphate solutions, while retaining most of the ferric phosphate as a raw material for regeneration. In some embodiments of the present invention, in step S5, phosphoric acid is added to adjust the pH of the dissolution solution, and the reflux temperature is 75–90°C.
[0041] S6: Add alkaline earth metal nitrate to the filtrate from S5 and heat to 50-80℃ to precipitate alkaline earth metal phosphate. Then, filter and separate the precipitate at this temperature. In step S6, on the one hand, due to excess phosphorus, phosphorus needs to be recovered. This is achieved by precipitating alkaline earth metal phosphate and converting it into phosphate fertilizer. On the other hand, alkaline earth metal phosphate is slightly soluble in the filtrate at a low concentration, which is beneficial for its presence as a dopant in the final regenerated lithium iron phosphate, thus enhancing its conductivity. In some embodiments of the present invention, the alkaline earth metal nitrate in step S6 is calcium nitrate and / or magnesium nitrate, and the amount added depends on the amount of phosphoric acid added in steps S2-S5, aiming to precipitate the phosphoric acid.
[0042] S7: Add sodium carbonate aqueous solution to the lithium-containing filtrate obtained in S6, and control the concentration of sodium carbonate to make the pH value between 9 and 11 to obtain lithium carbonate precipitate, and wash and dry it; the concentration range of sodium carbonate is specifically 1 mol / L-3 mol / L, and more preferably 1.5-2.5 mol / L.
[0043] S8: Add the iron phosphate obtained in S5 and the lithium carbonate obtained in S7 to an organic acid solution, grind and stir for 30-60 min, then dry the mixture, granulate it, and calcine it at 600-700℃ for 4-8 h to obtain regenerated lithium iron phosphate material. In this step, the organic acid ionizes to release hydrogen ions, making the iron phosphate and lithium carbonate easier to grind. This allows the particles to quickly reach the required nanoscale size under the combined action of chemical and mechanical grinding. In step S8, the iron phosphate and lithium carbonate are ground to an average particle size of 100-500 nm, more preferably 150-300 nm. The organic acid is at least one of acetic acid and maleic anhydride. Simultaneously, in step S8, a carbon source is further added and mixed and stirred. By coating the regenerated lithium iron phosphate, its conductivity is further improved. The carbon source is selected from at least one of glucose and sucrose.
[0044] Example 1
[0045] A process for extracting degraded ternary lithium battery cathode material includes the following steps:
[0046] S1: Disassemble and grade the lithium iron phosphate battery to obtain 1 kg of degraded lithium iron phosphate cathode material for later use;
[0047] S2: Grind the degraded lithium iron phosphate cathode material to an average particle size of 200 mesh, then mix it with about 10 L of 0.5 mol / L phosphoric acid solution, and sonicate it for 30 min. Let it stand, separate the upper clear liquid, and retain the lower homogeneous slurry treated with phosphoric acid.
[0048] S3: Load the slurry onto a porous conductive carbon substrate with an average pore size of 100 μm, compact it to remove the remaining phosphoric acid residue, dry it to prepare an anode, and recover the phosphoric acid solution from steps S2 and S3 for later use.
[0049] S4: Using an acid-resistant stainless steel plate as the cathode, the phosphoric acid solution recovered in steps S2 and S3, along with the newly added phosphoric acid solution, is prepared to obtain 10L of electrolyte with a concentration of 0.5mol / L. Electrolysis is performed by applying a voltage of 1.5V. After about 2.5h, the concentrations of lithium ions and iron ions in the solution no longer change, and electrolysis is stopped.
[0050] S5: Adjust the pH of the dissolution solution to 1.5, then heat under reflux at a temperature of 75-80°C. After 4 hours, the ferric phosphate precipitate will no longer change. Filter and separate the precipitate for later use.
[0051] S6: Add 0.5 mol / L calcium nitrate to the filtrate from S5 and heat to 60°C until calcium phosphate precipitate no longer forms. Then, filter and separate the precipitate at 60°C.
[0052] S7: Add 1.5 mol / L sodium carbonate aqueous solution to the lithium nitrate filtrate obtained in S6, control the pH value of the solution at 10, obtain lithium carbonate precipitate, and wash and dry it;
[0053] S8: The iron phosphate obtained in S5 and the lithium carbonate obtained in S7 are added to a 5 wt% aqueous acetic acid solution and a 5 wt% aqueous sucrose solution, and ground and stirred for 60 min to obtain particles with an average particle size of 300 nm. Then, the mixture is dried, granulated, and calcined at 700 °C for 6 h to obtain 0.82 kg of regenerated lithium iron phosphate material, of which the calcium doping content is 0.4 wt% and the carbon coating content is 3.2 wt%.
[0054] Example 2
[0055] A process for extracting degraded ternary lithium battery cathode material includes the following steps:
[0056] S1: Disassemble and grade the lithium iron phosphate battery to obtain 1 kg of degraded lithium iron phosphate cathode material for later use;
[0057] S2: Grind the degraded lithium iron phosphate cathode material to an average particle size of 50 mesh, then mix it with a 1 mol / L phosphoric acid solution of about 10 L, and sonicate it for 60 min. Let it stand, separate the upper clear liquid, and retain the lower homogeneous slurry treated with phosphoric acid.
[0058] S3: Load the slurry onto a porous conductive carbon substrate with an average pore size of 12 μm, compact it to remove the remaining phosphoric acid residue, dry it to prepare an anode, and recover the phosphoric acid solution from steps S2 and S3 for later use.
[0059] S4: Using an acid-resistant stainless steel plate as the cathode, the phosphoric acid solution recovered in steps S2 and S3, along with the newly added phosphoric acid solution, is prepared to obtain 10L of electrolyte with a concentration of 1mol / L. Electrolysis is performed by applying a voltage of 3V. After about 2 hours, the concentrations of lithium ions and iron ions in the solution no longer change, and electrolysis is stopped.
[0060] S5: Adjust the pH of the solution to 2, then heat under reflux at a temperature of 80-85°C. After 3.5 hours, the ferric phosphate precipitate will no longer change. Filter and separate the precipitate for later use.
[0061] S6: Add a 0.5 mol / L calcium nitrate and a 0.5 mol / L magnesium nitrate solution with a volume ratio of 1:1 to the filtrate from S5, and heat to 75°C until calcium phosphate and magnesium phosphate no longer precipitate, then stop adding the solution and filter at 75°C.
[0062] S7: Add 2.5 mol / L sodium carbonate aqueous solution to the lithium nitrate filtrate obtained in S6, control the pH value of the solution at 11, obtain lithium carbonate precipitate, and wash and dry it.
[0063] S8: The iron phosphate obtained in S5 and the lithium carbonate obtained in S7 are added to a 5wt% aqueous acetic acid solution and a 5wt% aqueous glucose solution, and ground and stirred for 40 min to obtain particles with an average particle size of 200 nm. Then, the mixture is dried, granulated, and calcined at 600 °C for 8 h to obtain 0.85 kg of regenerated carbon-coated lithium iron phosphate material, wherein the calcium doping content is 0.35 wt%, the magnesium doping content is 0.38 wt%, and the carbon coating content is 2.5 wt%.
[0064] Example 3
[0065] A process for extracting degraded ternary lithium battery cathode material includes the following steps:
[0066] S1: Disassemble and grade the lithium iron phosphate battery to obtain 1 kg of degraded lithium iron phosphate cathode material for later use;
[0067] S2: Grind the degraded lithium iron phosphate cathode material to an average particle size of 500 mesh, then mix it with about 10 L of 0.3 mol / L phosphoric acid solution, and sonicate it for 45 min. Let it stand, separate the upper clear liquid, and retain the lower homogeneous slurry treated with phosphoric acid.
[0068] S3: Load the slurry onto a porous conductive carbon substrate with an average pore size of 180 μm, compact it to remove the remaining phosphoric acid residue, dry it to prepare an anode, and recover the phosphoric acid solution from steps S2 and S3 for later use.
[0069] S4: Using an acid-resistant stainless steel plate as the cathode, the phosphoric acid solution recovered in steps S2 and S3, along with the newly added phosphoric acid solution, is prepared to obtain 10L of electrolyte with a concentration of 0.3mol / L. Electrolysis is performed by applying a voltage of 2V. After about 4 hours, the concentrations of lithium ions and iron ions in the solution no longer change, and electrolysis is stopped.
[0070] S5: Adjust the pH of the dissolution solution to 2, then heat under reflux, controlling the reflux temperature between 85-90℃. After 7 hours, the ferric phosphate precipitate will no longer change. Filter and separate the precipitate for later use.
[0071] S6: Add 0.5 mol / L magnesium nitrate to the filtrate from S5 and heat to 80°C until magnesium phosphate precipitate no longer precipitates. Then filter and separate the precipitate at 80°C.
[0072] S7: Add 1.5 mol / L sodium carbonate aqueous solution to the lithium nitrate filtrate obtained in S6, control the pH value of the solution at 9, obtain lithium carbonate precipitate, and wash and dry it;
[0073] S8: Add the iron phosphate obtained in S5 and the lithium carbonate obtained in S7 to a 5wt% aqueous acetic acid solution and grind and stir for 30 min to obtain particles with an average particle size of 500 nm. Then, dry and granulate the mixture and calcine it at 650℃ for 4 h to obtain 0.88 kg of regenerated lithium iron phosphate material, of which the magnesium doping content is 0.45 wt% and the carbon coating content is 2.8 wt%.
[0074] Example 4
[0075] A process for extracting degraded ternary lithium battery cathode material includes the following steps:
[0076] S1: Disassemble and grade the lithium iron phosphate battery to obtain 1 kg of degraded lithium iron phosphate cathode material for later use;
[0077] S2: Grind the degraded lithium iron phosphate cathode material to an average particle size of 400 mesh, then mix it with about 10 L of 0.5 mol / L phosphoric acid solution, and sonicate it for 30 min. Let it stand, separate the upper clear liquid, and retain the lower homogeneous slurry treated with phosphoric acid.
[0078] S3: Load the slurry onto a porous conductive carbon substrate with an average pore size of 60 μm, compact it to remove the remaining phosphoric acid residue, dry it to prepare an anode, and recover the phosphoric acid solution from steps S2 and S3 for later use.
[0079] S4: Using an acid-resistant stainless steel plate as the cathode, the phosphoric acid solution recovered in steps S2 and S3, along with the newly added phosphoric acid solution, is prepared to obtain 10L of electrolyte with a concentration of 0.5mol / L. Electrolysis is performed by applying a voltage of 4V. After about 2 hours, the concentrations of lithium ions and iron ions in the solution no longer change, and electrolysis is stopped.
[0080] S5: Adjust the pH of the dissolution solution to 1.5, then heat under reflux at a temperature of 75-80°C. After 3 hours, the ferric phosphate precipitate will no longer change. Filter and separate the precipitate for later use.
[0081] S6: Add a 0.5 mol / L calcium nitrate and a 0.5 mol / L magnesium nitrate solution with a volume ratio of 1:1 to the filtrate from S5 and heat to 70°C until calcium phosphate precipitate no longer precipitates. Then, filter and separate the precipitate at 70°C.
[0082] S7: Add 2.5 mol / L sodium carbonate aqueous solution to the lithium nitrate filtrate obtained in S6, control the pH value of the solution at 11, obtain lithium carbonate precipitate, and wash and dry it.
[0083] S8: Add the iron phosphate obtained in S5 and the lithium carbonate obtained in S7 to a 5wt% acetic acid aqueous solution, grind and stir for 40 min to obtain particles with an average particle size of 400 nm. Then, dry and granulate the mixture and calcine it at 650℃ for 5 h to obtain 0.78 kg of regenerated lithium iron phosphate material, of which the calcium doping content is 0.41 wt% and the magnesium doping content is 0.44 wt%.
[0084] The above embodiments are merely examples of implementation methods of the invention. The scope of protection of the present invention is not limited to the above embodiments. For those skilled in the art, several modifications and improvements can be made without departing from the concept of the present invention, and these all fall within the scope of protection of the present invention.
Claims
1. A process for dismantling and recycling lithium iron phosphate batteries, characterized in that, Includes the following steps: S1: Disassemble and grade the lithium iron phosphate battery to obtain degraded lithium iron phosphate cathode material for later use; S2: Grind the degraded lithium iron phosphate cathode material, then mix it with phosphoric acid solution, and sonicate it. Let it stand, separate the upper clear liquid, and retain the lower uniform slurry treated with phosphoric acid. S3: Load the slurry onto the positive electrode substrate, compact it to remove the remaining phosphoric acid residue, dry it to prepare the anode, and recover the phosphoric acid solution from steps S2 and S3 for later use. S4: Select an acid-resistant stainless steel plate as the cathode, use the phosphoric acid solution from steps S2 and S3 as the electrolyte, apply voltage to perform electrolysis until lithium and iron in the positive electrode slurry dissolve. S5: Adjust the pH of the dissolution solution to 1.5~2, then heat under reflux for 3~8 hours to precipitate ferric phosphate, and then filter and separate it for later use; S6: Add alkaline earth metal nitrate to the filtrate from S5 and heat to 50-80℃ to precipitate alkaline earth metal phosphate. Then, filter and separate the precipitate at this temperature. S7: Add sodium carbonate aqueous solution to the lithium-containing filtrate obtained in S6, and control the concentration of sodium carbonate to keep the pH value between 9 and 11 to obtain lithium carbonate precipitate, and wash and dry it. S8: Add the iron phosphate obtained in S5 and the lithium carbonate obtained in S7 to an organic acid solution, grind and stir for 30-60 minutes to obtain a mixture, then dry the mixture, granulate it and calcine it at 600-700℃ for 4-8 hours to obtain regenerated lithium iron phosphate material. In step S2, the phosphoric acid solution is partially derived from the phosphoric acid solution recovered in step S3, and the concentration of the phosphoric acid solution is prepared to be 0.2-1.5 mol / L. In step S5, the pH of the dissolution solution is adjusted by adding phosphoric acid, and the reflux temperature is 75-90℃.
2. The process according to claim 1, characterized in that, In step S2, the degraded lithium iron phosphate cathode material is ground to 50-500 mesh, ultrasonically treated for 20-60 minutes, and left to stand for 2-24 hours.
3. The process according to claim 1, characterized in that, The positive electrode substrate mentioned in step S3 is a porous conductive carbon material, and the average pore size of the porous material is 10-200 μm.
4. The process according to claim 1, characterized in that, In step S4, the voltage applied during electrolysis is 1V-4V, and the concentrations of lithium ions and iron ions in the solution are monitored until the concentrations no longer change.
5. The process according to claim 1, characterized in that, The alkaline earth metal nitrates in step S6 are calcium nitrate and / or magnesium nitrate.
6. The process according to claim 1, characterized in that, In step S7, the concentration of sodium carbonate ranges from 1 mol / L to 3 mol / L.
7. The process according to claim 1, characterized in that, In step S8, iron phosphate and lithium carbonate are ground to an average particle size of 100-500 nm, and the organic acid is at least one of acetic acid and maleic anhydride; in step S8, a carbon source is further added and mixed and stirred, and the carbon source is selected from at least one of glucose and sucrose.
8. A recycled lithium iron phosphate material prepared by the process according to any one of claims 1-7.
Citation Information
Patent Citations
A method for preparing lithium carbonate from crude lithium phosphate
CN109264748B
Methods for recovering ferrophosphate alloys and lithium compounds from waste lithium iron phosphate materials
CN109811125B
Method for preparing battery-grade iron phosphate and industrial-grade lithium phosphate in waste lithium iron phosphate battery
CN109775678A
Method for recovering metal ions in lithium iron phosphate waste through solid-phase electrolysis
CN111411366A
Lithium iron phosphate material as well as preparation method and application thereof
CN113104829A
